0095 Sleep Boosts Schema-Related Memory Consolidation and Inference. (27th May 2020) - Golkashani, H A; Chee, M W
Abstract: Introduction: A schema is a previously learned framework of information that helps the learning and retention of new, but related material. We examined how sleep, compared to staying awake following the acquisition of a schema, and thereafter novel material, affects the consolidation of new memoranda that were either embedded or not into the learned schema. We also tested if sleep affects the inference of hierarchy within these memoranda. Methods: 54 adolescents (mean age 16.6 years; 26 males) learned the age hierarchy of 7 galaxies by viewing adjacent pairs, one at a time e.g. A-B, D-E, and making transitive inferences (If B>C and C>D then B>D). Once this schema was learned to criterion, participants learned two new sets of galaxies: one set comprised 5 galaxies from the schema and 4 new, intercalated galaxies; the other contained 9 unfamiliar galaxies (schema & no-schema conditions). Memory for galaxy ordering was tested immediately after learning and again after 12-hours. One group(n=25) was kept awake in the day, while the other group (n=29) slept overnight for 8-h. Memory was tested for galaxies that were directly adjacent e.g. A-B, as well as for 'inference pairs' that were two apart: e.g.:(B-D, C-E). Results: Change in memory following the respective 12-hour intervals was analyzed using a mixed ANOVA with schema (schema, no-schema) and pair-type (adjacent, inference) as within-subject factors and sleep group (sleep/awake) as the between-subjects factor. There were significant main effects of sleep and pair type as well as a significant interaction, where schema-related memory was better preserved in the sleep group. This group also had higher performance for inference pairs embedded within the original schema. Conclusion: Sleep benefitted the consolidation of new memoranda embedded in a schema. This benefit was stronger for non-adjacent inference pairs suggesting that sleep boosts insight into non-explicitly declared, hierarchically organized information. Support: Supported by NMRC/STaR/0015/2013 and NRF2016-SOL002-001